Chemical and Biological Control of Sclerotium rolfsii in Grapevine Nurseries - Keyser, Helena A.; Ferreira, J.H.S. (South African Journal of Enology and Viticulture, 2017)
Laboratory and glasshouse trials were conducted to determine the efficacy of Bacillus subtilis, Gliocladium virens and different concentrations of the fungicide quintozene (75% WP) against Sclerotium rolfsii, causing death of grapevines in nurseries. Bacillus subtilis treatment considerably reduced the growth of S. rolfsii in vitro compared to the control. Quintozene at concentrations of 0,4, 1,2, 2,0, and 3,2 g per litre mixed with PDA totally suppressed the growth of S. rolfsii. In the glasshouse B. subtilis gave poor control. G. virens reduced mortality of grapevine plants caused by S. rolfsii, while no mortality of plants occurred when vines or soil was treated with quintozene. Quintozene at a concentration of 2% can be recommended as control measure against S. rolfsii in nurseries.